Parity-violating asymmetry and dipole polarizabilities in atomic nuclei: How do they reconcile with each other? - Roca-Maza Xavier (EPJ Web of Conferences)
In the recent years, considerable attention has been paid to the measurement of the dipole polarizability and parity violating asymmetry in medium and heavy mass nuclei such as 48Ca and 208Pb [1–4]. These two observables, as it already happened for the neutron skin thickness, are thought to be particularly sensitive to the properties of the nuclear equation of state at densities around nuclear saturation [5]. Hence, the interest in the low energy nuclear physics community to foster the needed experimental and theoretical developments to accurately study these two observables. In this proceeding I will briefly overview our recent theoretical analysis of the parity violating asymmetry and electric dipole polarizability [6–10].